Characterization of the inositol monophosphatase gene family in Arabidopsis - Nourbakhsh, Aida; Collakova, Eva; Gillaspy, Glenda E. (Frontiers in Plant Science, 2015)
Synthesis of myo-inositol is crucial in multicellular eukaryotes for production of phosphatidylinositol and inositol phosphate signaling molecules. The myo-inositol monophosphatase (IMP) enzyme is required for the synthesis of myo-inositol, breakdown of inositol (1,4,5)-trisphosphate, a second messenger involved in Ca2+ signaling, and synthesis of L-galactose, a precursor of ascorbic acid. Two myo-inositol monophosphatase -like (IMPL) genes in Arabidopsis encode chloroplast proteins with homology to the prokaryotic IMPs and one of these, IMPL2, can complement a bacterial histidinol 1-phosphate phosphatase mutant defective in histidine synthesis, indicating an important role for IMPL2 in amino acid synthesis. To delineate how this small gene family functions in inositol synthesis and metabolism, we sought to compare recombinant enzyme activities, expression patterns, and impact of genetic loss-of-function mutations for each. Our data show that purified IMPL2 protein is an active histidinol-P phosphatase enzyme in contrast to the IMPL1 enzyme, which has the ability to hydrolyze D-galactose 1-P, and D-inositol 1-P, a breakdown product of inositol (1,4,5)-triphosphate. Expression studies indicated that all three genes are expressed in multiple tissues, however, IMPL1 expression is restricted to above-ground tissues only. Identification and characterization of impl1 and impl2 mutants revealed no viable mutants for IMPL1, while two different impl2 mutants were identified and shown to be severely compromised in growth, which can be rescued by histidine. Analyses of metabolite levels in impl2 and complemented mutants reveals impl2 mutant growth is impacted by alterations in the histidine biosynthesis pathway, but does not impact myo-inositol synthesis. Together, these data indicate that IMPL2 functions in the histidine biosynthetic pathway, while IMP and IMPL1 catalyze the hydrolysis of inositol- and galactose-phosphates in the plant cell.